Corporate social responsibility and its impact on environmental sustainability - Ali Adel; Jafaar Aqeel Al-Jomaily; Duha Khalil Ibrahim Ahmed; Rasha Abdulkhaliq Abduljabbar Al-Dargazaly; Khdier Salman (Environment and Social Psychology, 2025)
The concept of Corporate Social Responsibility (CSR) has emerged as a very important driver of environmental sustainability that impacts corporate strategies across sectors. This study evaluates the impact of Corporate Social Responsibility (CSR) initiatives on environmental performance, focusing on key indicators such as greenhouse gas emissions, energy efficiency, waste management, and water conservation. Drawing on a rich dataset of 2015–2024 for multiple firms in the manufacturing, technology, energy, retail and healthcare industries, the study assesses the effectiveness of CSR. Using paired t-tests and regression modeling, we confirm through sophisticated statistical analyses that CSR investment is significantly associated with environmental enhancement, in particular, reductions in emissions and improvements in energy efficiency. The manufacturing and technology sectors showed the most significant growth; these have typically been boosted by progress in sustainability technologies and process improvements. On the other hand, energy and healthcare sectors showed moderate upgradation, limited by operations and regulations hurdles. The results, which demonstrate ROI across the board, speak to CSR’s financial viability and reinforce that CSR is an environmental and economic necessity. However, challenges such as inconsistencies in reporting and industries’ different peculiarities highlight the necessity for standardized CSR assessment frameworks. According to the study, businesses should embrace sustainability as part of their core strategies, while policymakers create clearer regulations that will drive corporate accountability. Future work could thus examine novel technology for sustainability, and relative CSR successes among diverse regulatory environments. The article shows significance of CSR activities leading towards achieving environmental sustainability and financial sustainability which are actionable for practitioners and stakeholders including policy makers and business owners.